Real-time low-cost industrial acquisition system - Silva, Vítor (2011)
Industrial systems monitor and control is, in the majority of the cases, implemented using real-time acquisition systems. Since the real-world is analog, there is a growing demand for faster, high resolution, real-time and reliable acquisition systems at very low cost. This paper presents an embedded system designed to tackle the previously listed requirements, thus being able to be used in most of today’s industrial systems requiring real-time data acquisition. The prototype developed, requires the co-design of hardware and software, the main difference and the main advantage offered is the added features and functionalities offered by the hardware platform used, such as USB connection (with the required real-time throughput), mass storage capability, database support and Ethernet connection. These features are supported by a Linux OS (uClinux). The embedded system developed is capable of acquiring eight analog channels simultaneously at 250kps for each channel with a 16-bit resolution, taking full advantage of the analog to digital converter (MAX11046). In order to do so several tailored drivers were programmed and added to the Linux kernel. Such a system can be used in many applications requiring real-time acquisition systems (medical, automotive, space exploration, etc).